Peritoneal histoplasmosis. Case report - Laura Marcela Fino-Velásquez; Fernán Santiago Zambrano-Muñoz; Alejandro Vega-Molina; Sebastián Felipe Sierra-Umaña; Silvio Javier Rosero-Paredes; Juan Esteban Barrios-Villegas; Juliana Arce-Cuervo; Laura Camila Urrutia-Corredor; Camilo Alejandro Díaz-Rojas (Case Reports)
Introduction: Histoplasmosis is an opportunistic granulomatous fungal infection. Peritoneal histoplasmosis (PH) is a rare form of disseminated histoplasmosis (DH). Case description: A 44-year-old male patient with history of HIV infection, systemic lupus erythematosus with lupus nephritis, and chronic kidney disease on peritoneal dialysis, presented with recurrent ascites without clear etiology in the serial study of ascitic fluid. Contrast computed tomography of the abdomen showed a nonspecific peritoneal nodule, for which laparoscopy and biopsy were performed, identifying Histoplasma capsulatum infection. The subject received 15 days of in-hospital treatment with amphotericin B deoxycholate with good evolution, no recurrence of ascites, and indefinite outpatient management with itraconazole. Discussion: The first case of PH was described in 1970 but this is the first case reported in Colombia. Most cases of PH have been associated with peritoneal dialysis. Its diagnosis is based on the study of ascitic fluid and its treatment follows the guidelines of other forms DH.